(untitled) (Research, Society and Development, 2024)
The Plan-Do-Check-Act (PDCA) cycle is a method that aims to continuously advance a company’s processes, products and services, enabling the stipulation of possibilities, enhancement of procedures and guarantee of inputs and tasks offered to customers. The objective of this study is to reduce the response time for service orders (SO) that arrive at the telephone sector in a Municipal Health Department (SMS) in Northeastern Brazil. The methodology applied was a narrative review of the literature regarding the PDCA tool with a qualitative and quantitative approach in order to reduce the response time for service orders. After this analysis, actions were taken to correct the flaws found. In the end, the result was an 81% reduction in the response time for service orders, thus preventing the accumulation of requests and improving the recognition of the SMS telephone sector by its users. The conclusion is that it is important to apply the PDCA tool in the analysis carried out to reduce the response time for service orders in the SMS telephony sector. However, even after these actions were carried out, the results found were mostly positive. However, there are still actions that must be redone and analyzed again within the PDCA tool in order to achieve an optimized result in which all failures are corrected.